Editorial for CLAWAR News -The Newsletter of CLAWAR Association - Vol. 18 - Huang, L (AUT University, 2008)
The theme of this issue continues in the same vein as that of Issue 17, which is of course our favourite hot topic - the service robot. We also begin to bring you related news from New Zealand as well as Europe and other countries. Compared to the many robot power houses such as Japan, USA and Europe, then New Zealand, an island situated remotely from the main continents, seems to be a quiet spot on the map of robotics research in the world. In reality, there are a lot of active research activities being carried out, and amazing results achieved by the local researchers who are well known among the population for their DIY (Do It Yourself) spirit. The special features of the New Zealand economy (agriculture, animal husbandry and forestry, to name a few) opens up an exciting domain, and provides a new flavour for the research in service robots. One of the reports in this issue brings you a new robot which mimics the human food chewing process, which has been developed by a research team led by Professors Peter Xu and John Bronlund at Massey University. This is just one example of many service robots being developed in New Zealand.